Phosphorus-Containing Polymers as Sensitive Biocompatible Probes for 31P Magnetic Resonance - Lucie Kracíková; Ladislav Androvič; Iveta Potočková; Natalia Ziółkowska; Martin Vít; David Červený; Daniel Jirák; Richard Laga (Molecules, 2023)
The visualization of organs and tissues using 31P magnetic resonance (MR) imaging represents an immense challenge. This is largely due to the lack of sensitive biocompatible probes required to deliver a high-intensity MR signal that can be distinguished from the natural biological background. Synthetic water-soluble phosphorus-containing polymers appear to be suitable materials for this purpose due to their adjustable chain architecture, low toxicity, and favorable pharmacokinetics. In this work, we carried out a controlled synthesis, and compared the MR properties, of several probes consisting of highly hydrophilic phosphopolymers differing in composition, structure, and molecular weight. Based on our phantom experiments, all probes with a molecular weight of ~3–400 kg·mol−1, including linear polymers based on poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC), poly(ethyl ethylenephosphate) (PEEP), and poly[bis(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)]phosphazene (PMEEEP) as well as star-shaped copolymers composed of PMPC arms grafted onto poly(amidoamine) dendrimer (PAMAM-g-PMPC) or cyclotriphosphazene-derived cores (CTP-g-PMPC), were readily detected using a 4.7 T MR scanner. The highest signal-to-noise ratio was achieved by the linear polymers PMPC (210) and PMEEEP (62) followed by the star polymers CTP-g-PMPC (56) and PAMAM-g-PMPC (44). The 31P T1 and T2 relaxation times for these phosphopolymers were also favorable, ranging between 1078 and 2368 and 30 and 171 ms, respectively. We contend that select phosphopolymers are suitable for use as sensitive 31P MR probes for biomedical applications.